2021
DOI: 10.1139/cjfas-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling risks to an endangered fish: using a state-space life cycle model to separate natural mortality from anthropogenic losses

Abstract: State-space population models are becoming a common tool to guide natural resource management, because they address the statistical challenges arising from high observation error and process variation while improving inference by integrating multiple, disparate datasets. A hierarchical state-space life cycle model was developed, motivated by delta smelt (Hypomesus transpacificus), an estuarine fish experiencing simultaneous risks of entrainment mortality from out-of-basin water export and natural mortality. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…We will refer to the β,0$$ {\beta}_{\cdot, 0} $$ as “intercept” parameters and β,1,β,2,...$$ {\beta}_{\cdot, 1},{\beta}_{\cdot, 2},\dots $$ as “slope” parameters, even though on the untransformed scale the vital rate curves are not linear. Alternative formulations for how ρt$$ {\rho}_t $$ and ϕi,t$$ {\phi}_{i,t} $$ are represented for this type of model were given by Maunder and Deriso (2011) and Smith et al (2021). The quantity Nn,0$$ {N}_{n,0} $$ may be treated as a parameter.…”
Section: Population Modelmentioning
confidence: 99%
“…We will refer to the β,0$$ {\beta}_{\cdot, 0} $$ as “intercept” parameters and β,1,β,2,...$$ {\beta}_{\cdot, 1},{\beta}_{\cdot, 2},\dots $$ as “slope” parameters, even though on the untransformed scale the vital rate curves are not linear. Alternative formulations for how ρt$$ {\rho}_t $$ and ϕi,t$$ {\phi}_{i,t} $$ are represented for this type of model were given by Maunder and Deriso (2011) and Smith et al (2021). The quantity Nn,0$$ {N}_{n,0} $$ may be treated as a parameter.…”
Section: Population Modelmentioning
confidence: 99%
“…Recent population modeling by Kimmerer and Rose (2018) and Smith et al (2021) has provided some direct quantitative insight into Delta Smelt population growth rates by comparing changes in growth rates between a limited set of scenarios reflecting different habitat conditions. The former study focused on the relative influence of food availability versus entrainment throughout the affected parts of the life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, several lines of evidence suggest a role of food limitation in the population dynamics of Delta Smelt. Mean fork length declined for a number of years shortly after the overbite clam invasion (Bennett 2005); adult mortality is correlated with prey abundance (Mac Nally et al 2010; Maunder and Deriso 2011; Smith et al 2021), and histopathologic assessments have shown evidence for frequent depletion of liver glycogen reserves (Hammock et al 2015; Teh et al 2020). Delta Smelt food limitation may be particularly acute in the summer, when water temperatures often reach physiologically stressful levels (Komoroske et al 2016) and the seasonal maximum of overbite clam grazing limits accumulation of plankton in the upper estuary (Kimmerer and Thompson 2014; Kimmerer et al 2019).…”
Section: Introductionmentioning
confidence: 99%